ITEM ANALYSIS OF READING COMPREHENSION TEST FOR POST-GRADUATE STUDENTS - Ari Arifin Danuwijaya (University of Kuningan, 2018)
Developing a test is a complex and reiterative process which subject to revision even if the items were developed by skilful item writers. Many commercial test publishers need to conduct test analysis, rather than trusting the item writers’ judgement and skills to improve the quality of items that need to be proven statistically after trying out was performed. This study is a part of test development process which aims to analyse the reading comprehension test items. One hundred multiple choice questions were pilot tested to 50 postgraduate students in one university. The pilot testing was aimed to investigate item quality which can further be developed better. The responses were then analysed using Classical Test Theory and using psychometric software called Lertap. The results showed that item difficulty level was mostly average. In terms of item discrimination, more than half of the total items were categorized marginal which required further modifications. This study suggests some recommendation that can be useful to improve the quality of the developed items. Keywords: reading comprehension; item analysis; classical test theory; item difficulty; test development.